2018
DOI: 10.3390/jcm7020024
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Erythropoietin Receptors in the Nervous System

Abstract: In addition to its regulatory function in the formation of red blood cells (erythropoiesis) in vertebrates, Erythropoietin (Epo) contributes to beneficial functions in a variety of non-hematopoietic tissues including the nervous system. Epo protects cells from apoptosis, reduces inflammatory responses and supports re-establishment of compromised functions by stimulating proliferation, migration and differentiation to compensate for lost or injured cells. Similar neuroprotective and regenerative functions of Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 207 publications
(260 reference statements)
2
78
0
Order By: Relevance
“…New neuroprotectants that have a therapeutic effect and cause no adverse effects are important for the treatment for patients with neurodegenerative diseases. Recently, a number of small molecules, including recombinant proteins such as neurotrophic factors, growth factors, erythropoietin, and anti-amyloid β antibody, have also been developed for neuroprotection [41][42][43]. However, their clinical applications are limited by the appearance of serious side effects such as cerebral vasculitis and stroke, poor bioavailability, and low bloodbrain barrier permeability [44].…”
Section: Discussionmentioning
confidence: 99%
“…New neuroprotectants that have a therapeutic effect and cause no adverse effects are important for the treatment for patients with neurodegenerative diseases. Recently, a number of small molecules, including recombinant proteins such as neurotrophic factors, growth factors, erythropoietin, and anti-amyloid β antibody, have also been developed for neuroprotection [41][42][43]. However, their clinical applications are limited by the appearance of serious side effects such as cerebral vasculitis and stroke, poor bioavailability, and low bloodbrain barrier permeability [44].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Particularly, it was also found that EPO stimulates proliferation and differentiation of skeletal muscle myoblasts, suggesting that the skeletal muscle might act as one of its targets. 10,11 Particularly, it was also found that EPO stimulates proliferation and differentiation of skeletal muscle myoblasts, suggesting that the skeletal muscle might act as one of its targets.…”
Section: Introductionmentioning
confidence: 99%
“…Erythropoietin (EPO) is known to have a wide range of therapeutic effects, such as anti-apoptosis, anti-oxidation, anti-inflammation and maintenance of vascular structure, as well as normal function. 10,11 Particularly, it was also found that EPO stimulates proliferation and differentiation of skeletal muscle myoblasts, suggesting that the skeletal muscle might act as one of its targets. 12,13 EPO might promote pro-myoblast effects through the activation of the same signaling cascades in hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is now thought that EPO's tissue-protective effects may be mediated through a separate heterodimeric receptor, consisting of one EPO subunit and one beta-common receptor (βCR) subunit (Brines et al, 2004;. Still, no study to date has demonstrated the interaction of EPO with this EPOR:βCR heterodimer, though a recently published article featuring a series of in silico experiments demonstrated the physical possibility of such an interaction based on protein and receptor conformations (Ostrowski & Heinrich, 2018). These authors suggest there may be additional substrates for EPO that have yet to be identified, as the proposed tissue protective receptor is not found in all cells that appear to benefit from EPO stimulation (Ostrowski & Heinrich, 2018).…”
Section: Epo In Animal Models Of Diseasementioning
confidence: 99%
“…Still, no study to date has demonstrated the interaction of EPO with this EPOR:βCR heterodimer, though a recently published article featuring a series of in silico experiments demonstrated the physical possibility of such an interaction based on protein and receptor conformations (Ostrowski & Heinrich, 2018). These authors suggest there may be additional substrates for EPO that have yet to be identified, as the proposed tissue protective receptor is not found in all cells that appear to benefit from EPO stimulation (Ostrowski & Heinrich, 2018). Although the molecular mechanisms by which EPO exerts its tissue-protective effects remain under investigation, researchers have recently begun to evaluate EPO's therapeutic potential in combination therapies for ischemia, as EPO's neuroprotective properties are well-established ).…”
Section: Epo In Animal Models Of Diseasementioning
confidence: 99%